Modi's dominance at G-20 summit Bali - Singh, M. K. (New Delhi Surendra Publications, 2023)
Prime Minister Narendra Modi reached Bali on November 14, 2022 evening to participate in the G-20 summit. In a pre-departure statement, Mr. Modi said that he will take up issues of "global concern" at the leadership level summit.
Keywords: Foreign policy; G-20 Summit; Prime Minister